Characteristics of gut microbiota in pigs with different breeds, growth periods and genders. Issue 3 (10th February 2021) - Wang, Cheng; Wei, Siyu; Chen, Nana; Xiang, Yun; Wang, Yizhen; Jin, Mingliang
Abstract: Gut microbiota plays important roles in host nutrition, metabolism and immunity, and is affected by multiple factors. However, the understandings of the gut microbiota in pigs within different breeds, growth periods and genders from a large cohort remain largely undefined. In the present study, the characteristics of the gut microbiota in 120 pigs of different breeds, growth periods and genders were investigated using the Illumina MiSeq PE300 combined with QIIME2 platform. A total of 7 388 636 raw reads and 16 411 features were obtained. Additionally, the microbial diversity, compositions and phenotypes were described. 66.53% microbiota belonged to the top 10 most abundant genera (pan gut bacteria), and 28 species were commonly identified (core gut bacteria, commonality ≥ 75%) among the pigs. Besides, the correlations within pan and core gut microbiota were firstly investigated. The metagenomic function was predicted by using PICRUSt2. Furthermore, the explanatory effects of the influencing factors suggested that growth period was the greatest contributor to the gut microbiota in pigs. These results expanded our knowledge of mammalian gut microbiota within different influencing factors and microbial‐related biological features in swine, which contributes to improving animal production and assisting animal model research. Abstract : The gut microbiota of 120 pigs of different breeds, growth periods and genders were characterized by newest platform. The pan and core microbiota of pigs were obtained. The effects of breeds, growth periods and genders on gut microbiota and their contributions were demonstrated.